THE EFFECT OF COMPENSATION SATISFACTION, SUPERVISOR SUPPORT ON TURNOVER INTENTION MEDIATED BY WORK ENGAGEMENT IN THE MANUFACTURING INDUSTRY IN BANTEN PROVINCE - Andari Andari; Nafiudin Nafiudin (Jurnal Ekonomi, 2022)
This study aims to determine and analyze the effect of compensation satisfaction, supervisor support on turnover intention mediated by work engagement. The research method used in this study is a quantitative method. The data analysis tool uses SMART PLS with the SPSS IBM 20.r program. The results of the study show that compensation satisfaction and supervisor support have no effect on turnover intention, while work engagement has an influence. Furthermore, work engagement is able to mediate compensation satisfaction and supervisor support on employee turnover intention in the Banten Province manufacturing industry.